一种变电站智能巡检系统 (2023)
本公开提供了一种变电站智能巡检系统，包括中控系统、多个巡检机器人以及在线监测设备；在线监测设备与变电站端综自系统连接，实时获取变电站端综自系统的遥信遥测数据，并实时反馈给中控系统；中控系统包括任务规划模块、路径规划模块；任务规划模块包括特殊巡检模块和周期性巡检模块，特殊巡检模块与在线监测设备连接，用于实时获取变电站端综自系统的遥信遥测数据，判断是否启动特殊巡检任务，并将判断结果传输给路径规划模块；周期性巡检模块，用于设定周期性巡检任务并传输给路径规划模块；通过获取变电站端综自系统的遥信遥测数据，来判断是否启动机器人特殊巡检，便于有针对性的进行巡检，提高了巡检机器人的巡检效率。 The invention provides an intelligent inspection system for a transformer substation. The intelligent inspection system comprises a central control system, a plurality of inspection robots and online monitoring equipment. The online monitoring equipment is connected with a transformer station end integrated automation system, obtains remote signaling and telemetering data of the transformer station end integrated automation system in real time, and feeds back the data to the central control system in real time. The central control system comprises a task planning module and a path planning module; the task planning module comprises a special inspection module and a periodic inspection module, and the special inspection mod